Sustainable Development Goals (SDGs), Tourism, and Sustainability in Bali - LAKSMI, Putu Ayu Sita; SAPUTRA, Komang Adi Kurniawan (Journal of Tourism Economics and Policy, 2025)
This study examines the implementation of Sustainable Development Goals (SDGs) in Bali’s tourism sector, analyzing the intersection of economic growth, environmental conservation, and cultural preservation. Through a mixed-methods approach combining surveys (300 respondents), stakeholder interviews (20 participants), and case studies (Nusa Penida and Ubud), the research identifies critical gaps in SDG awareness and sustainable practices. Findings reveal that while 68% of hotel managers demonstrate high SDG awareness, only 22% of respondents show strong knowledge of marine conservation (SDG 14). Sustainable practices exhibit partial adoption, with energy efficiency (42%) outperforming water conservation (29%) due to clearer economic incentives. Qualitative data highlights systemic challenges, including weak policy enforcement, cultural commodification, and power imbalances in multi-stakeholder collaboration. The study proposes a four-tier SDG integration framework, emphasizing: (1) strengthened government enforcement, (2) industry-wide certification standards, (3) community-led cultural guardianship, and (4) tourist education programs. Comparative analysis with Phuket and Boracay underscores Bali’s need for greater grassroots engagement, as only 28% of local businesses currently participate in sustainability initiatives—below Boracay’s 37%. Post-pandemic recovery trends further reveal a tension between mass tourism resurgence and opportunities for regenerative tourism models. These findings contribute to sustainable tourism literature by mapping Bali’s unique challenges onto global SDG targets. The research advocates for policy reforms that prioritize monitoring systems, economic incentives for green businesses, and cultural safeguarding measures. By addressing these gaps, Bali can transition from a mass tourism paradigm to a balanced model that aligns economic resilience with ecological and socio-cultural sustainability, offering lessons for island destinations globally.